Helping Local SME Suppliers Survive the Global Economic Crisis : Lessons from Zambia - Mwanza, Peter (World Bank, Washington, DC, 2012)
Economies dependent on resource extraction are particularly susceptible to sudden swings in commodity prices. International Finance Corporation (IFC) linkages projects should take this into account by helping small and medium enterprises (SMEs) prepare for the 'hard times,' such as the current global economic crisis, through diversification of markets and improving their coping capacities. To reduce their dependency on one or a limited number of corporations, SMEs should also be linked or introduced to market opportunities available from other organizations or firms. Likewise, other players or consumers in the sector should be included in 'crisis' planning and introduced to SMEs to increase the market size for SMEs. Finally, partnerships should be sought with government organizations involved in SME development to design innovative capacity-building interventions. This smart lesson describes how IFC's are helping Zambian SME suppliers hit hard by the global economic crisis and sharp fall in world copper prices and the lessons learned from the experience.